Evaluation of Ex-PRESS Mini Glaucoma Shunt Implantation with Preoperative Intracameral Bevacizumab Injection in Refractory Neovascular Glaucoma. Issue 6 (November 2016) - Guven Yilmaz, Suzan; Yildirim, Seyda; Degirmenci, Cumali; Ates, Halil
Purpose: To evaluate the efficacy and safety of Ex-PRESS mini glaucoma shunt implantation with preoperative intracameral bevacizumab injection in eyes with refractory neovascular glaucoma. Methods: A retrospective chart review of patients with medically uncontrolled neovascular glaucoma who had received 50-µL intracameral bevacizumab (1.25 mg) before undergoing Ex-PRESS mini glaucoma shunt implantation was performed. Success was defined as a postoperative intraocular pressure (IOP) between 5 and 21 mm Hg without (complete success) or with or without (qualified success) glaucoma medications and no additional glaucoma surgery, or loss of light perception. Results: In total, 33 eyes of 33 patients (15 female, 18 male) were enrolled in the study. The mean age of the study population was 61.2 years (range 36-78). The mean IOP decreased from 41.0 mm Hg (range 24-72) to 17.6 mm Hg (range 8-28) over a mean follow-up of 20.9 months (range 6-60) (p<0.001; Wilcoxon signed-rank test). Complete and qualified success rates were 36.4% and 66.7%, respectively. The average number of antiglaucoma medications decreased from 3.5 (range 2-4) preoperatively to 1.8 (range 1-4) postoperatively (p<0.001; Wilcoxon signed rank test). In 81.8% of cases, the decrease in IOP was 30% or more postoperatively. Conclusions: Ex-PRESS mini glaucoma shunt implantation with preoperative bevacizumab injection may be an effective alternative procedure for refractory neovascular glaucoma.